Impacto de los procesos administrativos en la eficiencia de la gestión pública en el GAD Municipal del cantón Penipe. - Miranda Quiñonez, Delia Karina (2025)
This research examines the impact of administrative processes on the efficiency of public management within the Decentralized Autonomous Government (GAD) of Penipe Canton. The core issue identified is a disconnect between formally established procedures and their actual implementation, resulting in operational inefficiencies, obstacles to achieving institutional goals, and a decline in the quality of public services delivered to citizens. The primary objective of the study was to assess the real impact of administrative processes on institutional performance and to propose strategies aimed at optimizing operational efficiency and promoting long-term organizational sustainability. To achieve this, a mixed methods approach was employed. The quantitative component involved surveys conducted with administrative personnel, while the qualitative phase included semi-structured interviews and an analysis of relevant regulatory documents. These methods enabled the collection of insights regarding the clarity, effectiveness, and compliance of key administrative processes, and offered a deeper understanding of the structural and cultural factors influencing their execution within the organizational environment. The findings highlighted several challenges: poor implementation of established processes, a lack of administrative innovation, limited technological resources, insufficient ongoing staff training, and interdepartmental fragmentation, all of which compromise traceability and institutional coordination. In response, the study proposes a process-based administrative management model grounded in the principles of process identification, standardization, automation, continuous improvement, and monitoring through institutional performance indicators. This model underscores the need for administrative modernization, strategic leadership, and a sustained commitment to continuous improvement to enhance efficiency and ensure sustainable governance.